The history of embalming in the era of anatomists of the XV-XVIII centuries - Svetlana Ninelievna, Chilingaridi; Sergey Evgenievich, Shemyakov; Vladimir Yefimovich, Milyukov; Elena Evgenevna, Nikiforova; Kheyalya Murshud Kizi, Sharifova; Elshan Rovshan Oglu, Sharifov; Cao Cuong, Nguyen (International Journal of Human Anatomy, 2023)
A historical review traces embalming practices and their role in anatomical study between the 15th and 18th centuries, connecting technique evolution to scientific milestones and ethics.
Keywords: Embalming; Anatomical Study; Ethics; Historical Review